Problematika vnitřního pnutí v materiálech při obrábění tenkostěnných dílů - Osička, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Diplomová práce se zabývá analýzu příčin vzniku zbytkového napětí v materiálech při čelním frézování. Měřením jsou porovnáváni zástupci tří skupin hliníkových slitin (5000, 6000, 7000). K měření zbytkového napětí hliníkových slitin je využita vyvrtávací metoda za použití tenzometrických růžic. K stanovení vlivu průměru fréz je využita porovnávací metoda na výsledné rovinnosti obrobené plochy. Práce je ukončena diskuzí s celkovým zhodnocením dosažených výsledků.

This master thesis focuses on analysing the origins of residual stress in material caused by face milling. Representatives of three groups of aluminum alloys (5000, 6000, 7000) are compared by measurements. For measuring of the residual stress in aluminum alloys, the hole-drilling method was used by applying tensometric rosettes. In order to determine the influence of the used milling cutters', flatness of the machined surface was analyzed by comparative method. The thesis concludes with a discussion and an overall evaluation of the results.
Issue of Internal Tension in Materials during Machining of Thin-walled Components
Keywords: Zbytkové napětí; čelní frézování; hliník; odvrtávací metoda; obrábění.; Residual stress; face milling; aluminum; holedrilling method; machining.